INVESMENT DESIRE : THE UTILIZATION TECHNOLOGY CHALLENGES AND THE INDIVIDUAL PERSONAL PERCEPTION - Hardiyanti, Siti Epa (Management Science Research Journal, 2023)
The research aims to test empirically: 1) the effect of perceived usefulness of technology use, perceived ease of use technology and individual perception towards investment desire on the people of Banten. 2) the effect of perceived usefulness of technology use and perceived ease of use technology on individual perception in the people of Banten, 3) the effect of perceived usefulness of technology use and perceived ease of use technology on investment desire in the people of Banten with the individual perception as an intervening variable. The object of research is the millennial generation in the people of Banten Province. In this study, the determination of the sample using the Slovin formula, a number of 123 respondents who have knowledge about investment and utilize technology to search investment information. This study uses Path Analysis techniques and data processing uses SPSS version 26. The results show that the perceived usefulness of technology use have effects on individual perception but does not effect to desire investment of the people of Banten Province. The results of hypothesis testing prove that the perceived ease of use technology does not effect on individual perception and desire investment on the people of Banten Province. The results of hypothesis testing prove that individual perception have an effect on investment desire at the people of Banten Province. The results of hypothesis testing prove that individual attitude can mediate the perceived usefulness of technology use on investment desire, but individual perception are not be able to mediate perceived ease of use technology on investment desire at the people of Banten Province.